THE INFLUENCE OF A SCHOOL BAG CARRIAGE ON THE PATTERN CHANGES IN PLANTAR PRESSURE DURING WALKING AMONG SCHOOLCHILDREN IN THE FIRST GRADE (Kinesiology, 2018)
The aim of this study was to determine the influence of the schoolbag carriage on pattern changes in plantar pressure during walking among schoolchildren in the first grade. The sample consisted of 127 schoolchildren, 48.8% male (N = 62) and 51.2% female (N = 65), with a mean age of 6.7 (± 0.5) years. The mean schoolbag weight was 4.2 kg (± 0.7), which represented a 16.9% (± 3.9) of the body weight, thus exceeds the upper limit of 15% of the body weight and can affect the posture by a general way.This study has shown a statistically significant influence of the school bag on changes in plantar pressure pattern when walking in relation to walking without the schoolbag. Using a t-test for large dependent samples and by setting statistical significance at p ≤ 0.05, a significant increase was noticed in peak pressure for the forefoot (p = .000; 17.1%), midfoot (p = .000; 5.7%) and the hindfoot (p = .004; 3.9%) as well as in average pressure for the midfoot (p = .005; 6.2%). Also, due to the compensatory mechanisms, while carrying the bag, a statistically significant increase in the contact surface at the forefoot (p = .000; 3.6%) and the midfoot (p =. 000, 8.8%) occurs. Changes in the distribution of pressure between the different parts of the foot are a source of potential foot problems which is why the results of this study have a high applicability in the prevention of foot pathology in the future.